Behind the Bureaucratic Wall: The Paradox of House of Worship Regulations in Indonesia - Rasiwan, Iwan; Kadir, ABD; Mantu, Rahman (Institut Agama Islam Negeri (IAIN) Manado, 2025)
Establishing houses of worship in Indonesia continues to face various obstacles despite constitutional guarantees. Data indicates an increasing trend in religious freedom violations, with 389 cases (2020-2021), 329 cases (2023), and 23 cases (2024), where rejection of house of worship establishments remains the predominant case. This research aims to critically analyze the implementation of the Joint Ministerial Regulation of the Minister of Religious Affairs and Minister of Home Affairs Numbers 9 and 8 of 2006 (PBM), focusing on three aspects: the causal relationship between administrative requirements and obstacles in establishing houses of worship, the impact of Religious Harmony Forum (FKUB) composition on the fulfillment of religious freedom rights, and formulating recommendations for simplifying house of worship establishment requirements. The research employs a socio-legal approach using the parameters of the Center for Religious Freedom and the International Covenant on Civil and Political Rights. Data was collected through in-depth interviews, documentation studies, and source triangulation. The research findings identify three main issues: quantitative requirements becoming structural barriers for minority groups, FKUB's majority-based representation composition creating bias in decision-making, and the decentralization of religious affairs leading to disparate treatment across regions. Policy reformulation is needed through simplifying administrative requirements, restructuring FKUB composition, and strengthening the central government's role in protecting religious freedom to realize the constitutional guarantee of religious freedom.